Production of functional bovine IL-22 in a mammalian episomal expression system - Klepp, Laura Ines; Bigi, María Mercedes; Villafañe, Luciana María; Blanco, Federico Carlos; Malinge, Pauline; Bigi, Fabiana (Elsevier, 2025)
Interleukin 22 is a member of the interleukin-10 superfamily of cytokines. This protein has a dual role as an inflammatory and anti-inflammatory molecule dependent on the context. IL-22 is produced mainly by immune cells and seems to have non-hematopoietic cells as its target. In this work, we report the production of bovine IL-22 for the first time in a semi-stable expression system in mammalian cells. We showed that this recombinant IL-22 possesses biological activity in bovine macrophages infected with Mycobacterium bovis and is easy to produce in large quantities. Given its role in the defence against infections, the IL-22 produced in this work has potential applications in scientific research as well as in immunotherapy to treat diseases in cattle.